A Descriptive Analysis of Using Cohesive Substitution Devices in Advanced EFLWriting - Qassim Ali, Assist. Prof. Dr. Ali (Basra studies journal, 2023)
This study aims to give a descriptive analysis of the cohesive substitution devices employed in advanced English as Foreign Language (EFL) writing. This research paper tries to determine the frequency and distribution of these cohesive devices that are used by advanced academic writers. The advanced EFL writers are from different countries: Iraq, Sudan, Iran, China, and Indonesia. The present study attempts to shed light on the EFL learners’ quality of writing by using such cohesive logical devices the main parts of any written text or discourse. To this end, the researcher uses five research papers or journals written by advanced learners about issues related to Applied Linguistics discipline. The section which is under the analysis is the “conclusion” section of these papers because it supposed to be short and has economical usage of language. Following Halliday and Hasan’s (1976) categorization of cohesive substitution devices, all uses of them are descriptively analyzed. The findings suggested that advanced EFL learners from different nations rarely use cohesive substitution devices in their academic writing.